2016
DOI: 10.11118/actaun201664020549
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Indirect Measurement Method of Seasonal Patterns of Leaf Area Index in a High-Density Short Rotation Coppice Culture of Poplar

Abstract: Leaf area index (LAI) is an important determinant of biomass production and yield of short rotation bio-energy plantation. An accurate measurement of LAI is critical for quantifying light interception and penetration within the canopy, and subsequently understanding its influence on the stand carbon and energy balance. The aim of the current study is validation of the Sunscan Plant Canopy Analyzer which serves as an indirect method for the evaluation of the seasonal patterns of LAI, relation between LAI and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
4
5
0
Order By: Relevance
“…The results of LAI development in SRC poplar show that the maximum occurs near the end of summer, which closely matches earlier studies for fast growing woody crops [27,47,60,61]. In these earlier studies, the LAI max ranged from 3.5-10 m 2 m −2 , which may be attributed to the growing season's weather conditions and development of poplar canopy [27,62].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The results of LAI development in SRC poplar show that the maximum occurs near the end of summer, which closely matches earlier studies for fast growing woody crops [27,47,60,61]. In these earlier studies, the LAI max ranged from 3.5-10 m 2 m −2 , which may be attributed to the growing season's weather conditions and development of poplar canopy [27,62].…”
Section: Discussionsupporting
confidence: 89%
“…Besides LAI development in SRC poplar and AFCs, our LAD results were similar to previous studies where the LAD range varied between 58 and 180 days in AFCs (C 3 and C 4 crops) and SRC [28,47,68,71]. Higher LAI and LAD were achieved in SRC poplar as compared to AFCs because woody crops are taller, multi stemmed, and their developed roots systems may accommodate higher canopy closure as compared to AFCs [25,26,54].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The leaf area index is regarded as one of the most important environmental parameters because it combines many ecological processes infl uencing the exchange of energy and matter between the ecosystem and the atmosphere [37][38]. Our study showed that the value of the leaf area index (LAI) varied in the consecutive years of the experiment (Table 5).…”
Section: Resultsmentioning
confidence: 94%